Evaluating the Outcomes of Active Surveillance in Grade Group 2 Prostate Cancer: Prospective Results from the Canary PASS Cohort. Issue 4 (2nd April 2022) - Waisman Malaret, Adrian J.; Chang, Peter; Zhu, Kehao; Zheng, Yingye; Newcomb, Lisa F.; Liu, Menghan; McKenney, Jesse K.; Brooks, James D.; Carroll, Peter; Dash, Atreya; Filson, Christopher P.; Gleave, Martin E.; et al.
Abstract : Purpose: Active surveillance (AS) for grade group (GG) 2 patients is not yet well defined. We sought to compare clinical outcomes of men with GG1 and GG2 prostate cancer undergoing AS in a large prospective North American cohort. Materials and Methods: Participants were prospectively enrolled in an AS study with protocol-directed followup at 10 centers in the U.S. and Canada. We evaluated time from diagnosis to biopsy grade reclassification and time to treatment. In men treated after initial surveillance, adverse pathology and recurrence were also analyzed. Results: At diagnosis, 154 (9%) had GG2 and 1, 574 (91%) had GG1. Five-year reclassification rates were similar between GG2 and GG1 (30% vs 37%, p=0.11). However, more patients with GG2 were treated at 5 years (58% vs 34%, p <0.001) and GG at diagnosis was associated with time to treatment (HR=1.41; p=0.01). Treatment rates were similar in patients who reclassified during AS, but in patients who did not reclassify, those diagnosed with GG2 underwent definitive treatment more often than GG1 (5-year treatment rates 52% and 12%, p <0.0001). In participants who underwent radical prostatectomy after initial surveillance, the adjusted risk of adverse pathology was similar (HR=1.26; p=0.4). Biochemical recurrence within 3 years of treatment for GG2 and GG1 patients was 6% for both groups. Conclusions: In patients on AS, the rate of definitive treatment is higher after an initial diagnosis of GG2 than GG1. Adverse pathology after radical prostatectomy and short-term biochemical recurrence after definitive treatment were similar between GG2 and GG1.